AN ANALYSIS OF NATIONAL IDEOLOGICAL CONSTRUCTS IN ENGLISH LANGUAGE TEXTBOOKS OF THE SINGLE NATIONAL CURRICULUM IN PAKISTAN - Imran Hussain; Dr. Ziarab Mehmood; Dr. Rubina Rahat (International Journal of Contemporary Issues in Social Sciences, 2024)
Aim/Purpose: To develop a scientific intellectual map that explores the relationship between social media marketing channel usage and corporate performance in the context of Pakistani SMEs. To highlight the unique challenges and opportunities faced by Pakistani SMEs in the digital landscape. Background: Existing research on social media marketing primarily focuses on large corporations. This study focuses on the specific context of Pakistani SMEs, acknowledging their unique characteristics and digital environment. Methodology: Review of past research on social media marketing and corporate performance in Pakistan. Development of a conceptual model with six constructs: social media marketing channel usage, corporate performance, cost reduction, marketing capabilities, innovation, and age of company. Quantitative research to test the proposed model. Contribution: Provides a comprehensive understanding of how social media marketing can enhance corporate performance in the Pakistani SME sector. Findings: Social media marketing channel usage significantly contributes to corporate performance in Pakistani SMEs. Cost reduction, marketing capabilities, and innovation mediate this relationship. The age of the company moderates the impact of social media marketing on corporate performance. Recommendations for Practitioners: Invest in robust social media marketing strategies tailored to the specific needs of Pakistani SMEs. Focus on enhancing marketing capabilities and fostering innovation to maximize the impact of social media. Implement cost reduction measures to optimize resource utilization and enhance profitability. Recommendations for Researchers: Conduct further empirical studies to validate the proposed model in different contexts. Explore the influence of other relevant factors, such as industry type and market competition. Consider the impact of cultural and socio-economic factors on social media marketing effectiveness in Pakistan. Impact on Society: This research contributes to the understanding of how digital technologies can empower Pakistani SMEs to compete in the global market. The findings can inform policy development and support initiatives to promote digital adoption among SMEs. Future Research: Longitudinal studies to track the long-term effects of social media marketing on SME performance. Qualitative research to explore the subjective experiences and challenges of Pakistani SMEs in the digital environment. Cross-cultural comparisons to understand the applicability of the proposed model in different contexts.